Condutas para reparação da cavidade anoftálmica no Brasil - De Sousa, Roberta Lilian Fernandes [UNESP]; Schellini, Silvana Artioli [UNESP]; Zornoff, Denise De Cássia Moreira [UNESP]; Padovani, Carlos Roberto [UNESP] (FapUNIFESP (SciELO), 2012)
Purpose: To determine the most common approach to repair the anophthalmic socket in Brazil, and to compare the data with the trends in other countries. Methods: Exploratory study using electronic questionnaire sent by Internet to ophthalmologists members of the Brazilian Orbit and Oculoplastic Society (SBCPO). The received answers were analyzed by adhesion analysis, using Chi-square test. Results: We received 75 answered questionnaires. Fifty-three per cent of the respondents frequently treat anophthalmic socket and use the 18 mm diameter polymethylmethacrylate sphere in the majority of the surgeries, mainly covered by sclera (92%). Only seven interviewees had used integrated implants with pegging procedure. Eighty-two per cent of the ophthalmologists use the dermolipid graft to reconstruct the anophthalmic socket. They also follow the patients bi-annually. Conclusions: The treatment of anophthalmic socket in Brazil generally involve polymethylmethacrylate sphere with 18 mm diameter. Pegging procedure is uncommon between us.
Trends on anophthalmic socket repair in Brazil
Keywords: Anophthalmos; Brazil; Eye artificial; Eye evisceration; Orbit